Time in colors: Capturing memory, past and life moments in painting. (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article discusses how time, memory, and moments of the past can be expressed in the art of painting. It discusses how artists “capture” life events through color and composition, and what emotions they fill them with. The article also analyzes the reflection of the concept of time in the human mind through color psychology and visual language.